Peranan Customer Service dan Promosi terhadap Keputusan Menggunakan Produk Tabungan Bank Nagari Cabang Pasar Raya Padang - Utari, Putri; Egim, Ash Shadiq (STIE Perbankan Indonesia, 2024)
This study aims to determine the influence of customer service and promotion partially and simultaneously on customer decisions to save at Bank Nagari Pasar Raya Branch. This study uses a quantitative type, the data used is primary data sourced from respondents who are used as samples using the Cohran method. The sample in this study amounted to 97 research respondents. The sample selection method used in this study is the incidental sampling technique which is classified as one of the non-probability sampling techniques. Hypothesis testing with multiple linear regression models. The results of the study are that Customer Service has a positive effect on the Decision to use savings products at Bank Nagari Pasar Raya Branch. Promotion has an effect on the Decision to use savings products at Bank Nagari Pasar Raya Branch. Based on the results of the t-test, it was found that the Promotion variable has the largest t-count value and beta coefficient. So that the Promotion variable has the strongest influence compared to other variables, the Promotion variable has a dominant influence on the Decision to use savings products at Bank Nagari. In addition, the determination test (R2) showed that the ability of the independent variables, namely Customer Service and promotion to the dependent variable, namely the decision to use savings products, was 75.7% while the remaining 24.3% was influenced by other variables that were not studied. Keywords: Purchasing Decision, Customer Service, Promotion, Bank Nagari.